Mapping Quantitative Trait Loci Controlling High Iron and Zinc Content in Self and Open Pollinated Grains of Pearl Millet [Pennisetum glaucum (L.) R. Br.] - Kumar, Sushil; Hash, Charles T.; Thirunavukkarasu, Nepolean; Singh, Govind; Rajaram, Vengaldas; Rathore, Abhishek; Senapathy, Senthilvel; Mahendrakar, Mahesh D.; Yadav, Rattan S.; Srivastava, Rakesh K. (Frontiers in Plant Science, 2016)
Pearl millet is a multipurpose grain/fodder crop of the semi-arid tropics, feeding many of the world’s poorest and most undernourished people. Genetic variation among adapted pearl millet inbreds and hybrids suggests it will be possible to improve grain micronutrient concentrations by selective breeding. Using 305 loci, a linkage map was constructed to map QTLs for grain [Fe] and [Zn] using replicated samples of 106 pearl millet RILs (F6) derived from ICMB 841-P3 × 863B-P2. The grains of the RIL population were evaluated for Fe and Zn concentration using atomic absorption spectrophotometer. Grain mineral concentrations ranged from 28.4-124.0 ppm for Fe and 28.7-119.8 ppm for Zn. Similarly,grain Fe and Zn in open pollinated seeds ranged between 22.4-77.4 and 21.9-73.7 ppm, respectively. Mapping with 305 (96 SSRs; 208 DArT) markers detected seven linkage groups covering 1749 cM (Haldane) with an average intermarker distance of 5.73 cM. On the basis of two environment phenotypic data, two co-localized QTLs for Fe and Zn density on LG 3 were identified by composite interval mapping (CIM). Fe QTL explained 19% phenotypic variation, whereas the Zn QTL explained 36% phenotypic variation. Likewise for open pollinated seeds, the QTL analysis led to identification of two QTLs for grain Fe density on LG 3 and 5, and two QTLs for grain Zn density on LG 3 and 7. The total phenotypic variance for Fe and Zn QTLs in open pollinated seeds was 16% and 42%, respectively. Analysis of QTL × QTL and QTL × QTL× environment interactions indicated no major epistasis.